Reflections of including key audit matters in the audit quality and audit fees of publicly traded companies in Brazil - Melo, Priscila dos Santos Fernandes (2024)
Considering the context of the changes implemented by the revised ISA 700, which required including items such as Key Audit Matters (KAMs), this article aimed to examine the effects of the changes in ISA 700 on audit quality and fees. Accounting and market data, information on the responsible audit firms, and the number of KAMs disclosed by publicly traded companies in Brazil were collected from 2014 to 2017. Overall, the results did not demonstrate evidence of improvement in audit quality after adopting the revised ISA 700. Audit fees also did not show statistically significant changes when comparing the period before and after adopting the new requirement. So, the study concluded that, during the four-year period surrounding the adoption of the new requirements, there was no evidence of an increase in audit quality or auditor fees for publicly traded companies in Brazil. This article expands academic discussions in the Brazilian capital market regarding the implications of including KAMs in audit reports, as well as the analysis of the practical effects of applying standards issued by regulatory bodies.